Analisa Kerusakan Jalan Akibat Beban Kendaraan di Gerbang Masuk Kota Jambi Paal 10 – Simpang 4 Paal 10 Kota Jambi - Das, Amsori M; Setiawan, Ari; Hurairah, Abi (Jurnal Talenta Sipil, 2024)
The Palembang - Jambi highway is a very busy route. Along the road at the entrance to Jambi City, Paal 10 - Simpang 4 Paal 10, Jambi City is passed by many vehicles because this road is one of the roads that is open to pass through heavy vehicles carrying loads. This is also one of the causes of rapid damage to flexible road pavement. The aim of this research is to determine the average daily traffic volume of vehicles passing through the asphalt pavement at the entrance gate of Jambi City, Paal 10 - intersection 4 Paal 10, Jambi City, to find out the effect of vehicle load on the level of road damage on the entrance gate of Jambi City. Paal 10 – Simpang 4 Paal 10 Jambi City. This research method uses guidelines from Bina Marga Pd T-14-2003. Average daily traffic data (LHR) on the entrance road to the city of Jambi Paal 10 – intersection 4 Paal 10 Jambi City on Saturday is 6,702 vehicles, on Sunday it is 6650 vehicles and on Monday it is 6719 vehicles. From this data, the total LHR from the vehicle analysis results is 1115 vehicles/hour. and the results of the Truck Factor calculation are 3.775 > 1, where this value shows that the condition of the damage to the road at the entrance to the city of Jambi Paal 10 - intersection 4 Paal 10 Jambi city is due to the excessive load of vehicles passing through it. The excessive load factor that occurs causes 2 types of damage, namely groove distortion with a high level of damage and alligator cracks.